THE ROLE OF HERBAL TO INCREASE THE BODY'S IMMUNE AS A PREVENTIVE FOR COVID 19 AND DISTRIBUTING MASKS - ahmad riadi (Wealth Community Empowerment, 2024)
Background: The role of herbal medicine in increasing body immunity as prevention of Covid 19 and distributing masks in the RW 28 area, Sendang Mulyo Village, Tembalang District, Semarang City. Objective: This community service is to increase the body's immunity and prevent the spread of Covid 19. The method used is by distributing herbs, masks and pocket books in the community. Results Based on the results of the evaluation carried out, it was concluded that this activity was very inviting to the public who took an active part in activities in the form of distributing herbs, masks and socializing the importance of maintaining body immunity in facing the Covid-19 pandemic. Conclusion: This activity can increase residents' insight into increasing immunity through consuming herbal medicines for the body and preventing Covid-19 by using masks